Topical Percutaneous Drug Delivery for Allergic Diseases: A Novel Strategy for Site-Directed Pharmacologic Modulation - Mitsuhiro Kamimura; Hiroaki Todo; Kenji Sugibayashi; Koichiro Asano (Pharmaceutics)
Topical percutaneous drug delivery has recently emerged as a novel strategy for the treatment of allergic diseases, offering targeted drug delivery to mucosal tissues adjacent to the skin. Unlike conventional topical approaches that act on the skin surface or mucosal membranes, topical percutaneous drug delivery enables non-invasive pharmacologic modulation of deeper structures such as the conjunctiva, nasal mucosa, and trachea. This review explores the rationale, pharmacokinetic foundation, clinical data, and future prospects of transdermal therapy in allergic conjunctivitis, allergic rhinitis, and asthma-related cough. In allergic conjunctivitis, eyelid-based transdermal delivery of antihistamines such as diphenhydramine and epinastine has shown rapid and long-lasting symptom relief, with epinastine cream recently approved in Japan following a randomized controlled trial (RCT) demonstrating its efficacy. Preclinical and clinical pharmacokinetic studies support the eyelid’s unique permeability and sustained drug release profile, reinforcing its utility as a delivery site for ocular therapies. In allergic rhinitis, diphenhydramine application to the nasal ala demonstrated symptomatic improvement in patients intolerant to intranasal therapies, though anatomical separation from the inflamed turbinates may limit consistent efficacy. Similarly, cervical tracheal application of steroids and antihistamines has shown potential benefit in asthma-related cough, especially for patients refractory to inhaled treatments, despite anatomical and depth-related limitations. Overall, site-specific anatomy, skin permeability, and disease localization are critical factors in determining therapeutic outcomes. While trans-eyelid therapy is supported by robust data, studies on the nasal ala and trachea remain limited to small-scale pilot trials. No major adverse events have been reported with nasal or tracheal application, but eyelid sensitivity requires formulation caution. To validate this promising modality, further RCTs, pharmacokinetic analyses, and formulation optimization are warranted. Topical percutaneous drug delivery holds potential as a non-invasive, site-directed alternative for managing allergic diseases beyond dermatologic indications.